2004
DOI: 10.1177/155005940403500303
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Acute Middle Cerebral Artery Ischemic Stroke by Quantitative Electric Tomography

Abstract: This paper focuses on the application of quantitative electric tomography (qEEGT) to map changes in EEG generators for detection of early signs of ischemia in patients with acute middle cerebral artery stroke. Thirty-two patients were studied with the diagnosis of acute ischemic stroke of the left middle cerebral artery territory, within the first 24 hours of their clinical evolution. Variable Resolution Electrical Tomography was used for estimating EEG source generators. High resolution source Z-spectra and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 72 publications
4
46
0
Order By: Relevance
“…Although this finding is observed in a small sample, it is consistent with high increases in delta activity and decreases in alpha activity in non-acute ABI patients reported by Nuwer et al (1987), and others (Tolonen, 1984;Machado et al, 2004;Finnigan et al, 2007). Our findings also extend the significance of this index to the chronic phase when sequelae are established.…”
Section: Discussionsupporting
confidence: 93%
“…Although this finding is observed in a small sample, it is consistent with high increases in delta activity and decreases in alpha activity in non-acute ABI patients reported by Nuwer et al (1987), and others (Tolonen, 1984;Machado et al, 2004;Finnigan et al, 2007). Our findings also extend the significance of this index to the chronic phase when sequelae are established.…”
Section: Discussionsupporting
confidence: 93%
“…Stuart et al also reported the alpha-delta ratio to be most predictive for DCI in intracortical EEG (Stuart et al, 2010). A possible explanation for the divergent findings may be the hypothesis corroborated by Machado et al (Machado et al, 2004) who applied qEEG to patients with MCA ischemic strokes and found delta power increases to be related to the ischemic core while the tissue at risk, penumbra, and edema were characterized by alpha and theta alterations. Correspondingly, the alpha decrease in our study marked the early point where perfusion dropped below a critical level, generating tissue at risk of, but not yet persistent, ischemic infarction.…”
Section: Discussionmentioning
confidence: 88%
“…The derivation of the CAI in our study was based on previous research which identified changes in the alpha band during ischemia notably in the penumbric region [14,15,34]. However, the use of alternate power bands and their ratios raises the possibility of a wide array of quantitative parameters that may be optimal markers of DCI [4,[34][35][36].…”
Section: Discussionmentioning
confidence: 98%
“…However, the use of alternate power bands and their ratios raises the possibility of a wide array of quantitative parameters that may be optimal markers of DCI [4,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%